A visibilidade do profissional tradutor/intérprete no ensino fundamental de escolas estaduais em Areia Branca-RN - Fernandes, Francisca Paula Victor (Universidade Federal Rural do Semi-Árido, 2020)
This work aims to report results on how libras interpreters working in two different schools in the state network are observed. Emphasize the mediating role of this professional in his educational work, as well as are perceived by the school, the conditions in which he performs his professional activity, and as he seeks elements to discuss the knowledge seen in the school environment. Thus, the methodology worked is a qualitative research, in the school environment on the vision of the practice of acting of the Sign Language interpreter. Thus, we conduct a study to know about how in the work environment this professional is understood, in socialization, in which they live with people who are hearing and deaf, aiming at knowledge and values in the process of knowledge and learning. After these surveys, some theoretical materials were studied, conducting a study of some works by authors related to the theme.
Monografia
Keywords: Surdo; Professor; Intérprete; Deaf; Teacher; Interpreter; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL